Treatment of Experimental Periodontal Disease by Photodynamic Therapy in Rats With Diabetes - Almeida, Juliano Milanezi de [UNESP]; Theodoro, Letícia Helena [UNESP]; Bosco, Álvaro Francisco [UNESP]; Nagata, Maria José Hitomi [UNESP]; Bonfante, Samara; Garcia, Valdir Gouveia [UNESP] (Amer Acad Periodontology, 2008)
Background: The aim of this study was to evaluate histologically and histometrically the influence of photodynamic therapy (PDT) as an adjuvant treatment on induced periodontitis in rats with diabetes.Methods: Two hundred forty rats were divided evenly into two groups: non-diabetic (ND; n = 120) and alloxan diabetic (D; n = 120). Periodontal disease was induced in both groups at the first mandibular molar. After 7 days, the ligature was removed, and all animals underwent scaling and root planing (SRP) and were divided according to the following treatments: irrigation with saline solution (SRP); irrigation with a phenothiazinium dye (100 mu g/ml) (TBO); laser irradiation (660 nm, 24 J) (LLLT); and PDT (TBO and laser irradiation). Ten animals in each experimental group and treatment subgroup were euthanized at 7, 15, and 30 days. The histometric values were analyzed statistically (P<0.05).Results: In the ND group, the animals treated by PDT showed less bone loss (0.33 +/- 0.05 mm(2), 0.35 +/- 0.06 mm(2), and 0.27 +/- 0.07 mm(2) at 7, 15, and 30 days, respectively; P<0.05) at all experimental periods than the SRP group (1.11 +/- 0.11 mm(2), 0.84 +/- 0.12 mm(2), and 0.97 +/- 0.13 mm(2) at 7, 15, and 30 days, respectively), the TBO group (0.51 +/- 0.12 mm(2), 0.70 +/- 0.13 mm(2), and 0.64 +/- 0.08 mm(2) at 7, 15, and 30 days, respectively), and the LLLT group (0.59 +/- 0.03 mm(2), 0.61 +/- 0.04 mm(2), and 0.60 +/- 0.03 mm(2) at 7, 15, and 30 days, respectively). In the D group, the animals treated by PDT showed less bone loss (0.29 +/- 0.03 mm(2), 0.24 +/- 0.02 mm(2), and 0.27 +/- 0.06 mm(2) at 7, 15, and 30 days, respectively; P<0.05) at all experimental periods than the SRP group (2.27 +/- 0.47 mm(2), 3.23 +/- 0.34 mm(2), and 2.82 +/- 0.75 mm(2) at 7, 15, and 30 days, respectively), the TBO group (0.51 +/- 0.15 mm(2),0.44 +/- 0.07 mm(2), and 0.57 +/- 0.13 mm(2) at 7,15, and 30 days, respectively), and the LLLT group (0.37 +/- 0.05 mm(2), 0.35 +/- 0.09 mm(2), and 0.39 +/- 0.12 mm(2) at 7, 15, and 30 days, respectively).Conclusion: PDT was a beneficial adjuvant treatment for periodontal diseases induced by bacterial plaque and systemically modified by diabetes mellitus. J Periodontol 2008,79:2156-2165.
Keywords: Animal studies; diabetes; lasers; periodontitis; photodynamic